The Courage of Truth - Foucault, M. author. aut Link
XVI, 364 p.
Keywords: The Courage of the Truth is the last course that Michel Foucault delivered at the College de France before his death in 1984. In this course, he continues the theme of the previous year's lectures in exploring the notion of "truth-telling" in politics to establish a number of ethically irreducible conditionsbased on courage and conviction.